2019
DOI: 10.3390/su11247053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate and Land-Cover Changes on Soil Erosion in Brazilian Pantanal

Abstract: The Pantanal biome integrates the lowlands of the Upper Paraguay Basin (UPB), which is hydrologically connected to the biomes of the Cerrado and Amazon (the highlands of the UPB). The effects of recent land-cover and land-use (LCLU) changes in the highlands, combined with climate change, are still poorly understood in this region. Here, we investigate the effects of soil erosion in the Brazilian Pantanal under climate and LCLU changes by combining different scenarios of projected rainfall erosivity and land-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 43 publications
0
21
0
3
Order By: Relevance
“…All these were not conducive to soil moisture supplement [24]. It has been reported that the water capacity of litter in heavily grazed grasslands is only 95% of that in native grasslands, and litter also proved to be the key control factor of soil water storage in this study [25]. The soil bulk density increased gradually under the trample action of grazing cattle and sheep [26], which reduced the pores in the soil and thereby was not conducive to soil moisture adsorption.…”
Section: Grazing Significantly Reduced Soil Water Storagementioning
confidence: 64%
“…All these were not conducive to soil moisture supplement [24]. It has been reported that the water capacity of litter in heavily grazed grasslands is only 95% of that in native grasslands, and litter also proved to be the key control factor of soil water storage in this study [25]. The soil bulk density increased gradually under the trample action of grazing cattle and sheep [26], which reduced the pores in the soil and thereby was not conducive to soil moisture adsorption.…”
Section: Grazing Significantly Reduced Soil Water Storagementioning
confidence: 64%
“…Muitos trabalhos abordam a erosão do solo em diversos aspectos como Mohammed et al (2020) que detectou a influência de diferentes declives nesse fenômeno do solo, Colman et al (2019) que observou os efeitos do clima associado com as mudanças do uso e cobertura da terra provoca processos erosivos principalmente em áreas com atividades agrícolas. desenvolveu um produto cartográfico que apresenta a vulnerabilidade do solo de uma bacia hidrográfica próxima da BHA, ratificando as linhas de pensamento dos autores anteriores de que o acelerado avanço do uso e ocupação da terra provoca a instabilidade do solo.…”
Section: Erosão Hídrica Do Solounclassified
“…Land-use/cover design and management at the watershed scale are major factors that control the amount of soil loss to water bodies [36][37][38][39]. On the other hand, the impacts of current riparian land-use on bank erosion at the field (reach) scale are still poorly understood due to varying temporal and spatial scale effects on stream hydro-morphology and the effects of connectivity of the stream channel process and riparian ecosystem [16,40,41].…”
Section: Impacts Of Land Use Within 50 M Strips On Either Side Of the Streammentioning
confidence: 99%